(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Pharmacoeconomic analysis is a method for assessing the rationality of the use of financial and pharmaceutical products in the healthcare system. It allows you to determine the most optimal options for using medications based on data on their cost and effectiveness. This article examines the role of pharmacoeconomic analysis in the health care system and its implications for decision-making on the best treatment strategies. It also emphasizes the importance of conducting such analysis as a means of improving the quality and accessibility of medical care, reducing treatment costs and increasing the economic efficiency of the health care system as a whole.